Molecular Basis of Inhibitory Activities of Berberine against Pathogenic Enzymes in Alzheimer's Disease - Hong-Fang Ji; Liang Shen (The Scientific World Journal)
The natural isoquinoline alkaloid berberine possesses potential to treat Alzheimer's disease (AD) by targeting multiple pathogenic factors. In the present study, docking simulations were performed to gain deeper insights into the molecular basis of berberine's inhibitory effects against the important pathogenic enzymes of AD, that is, acetylcholinesterase, butyrylcholinesterase, and two isoforms of monoamine oxidase. It was found that the theoretical binding affinities of berberine to the four enzymes are very close to the experimental values, which verify the methodology. Further inspection to the binding modes found that hydrophobic interactions between the hydrophobic surface of berberine and neighboring hydrophobic residues are the principal forces contributing to the ligand-receptor interactions. Although berberine cation also has potential to form electrostatic interaction with neighboring residues, it is interesting to find that electrostatic force is excluded in the four cases unexpectedly. These results have important implications for the berberine-based anti-AD drug design.